Deep Learning Paradigm In The Context Of Multicultural Education In Indonesia - Nurul Musfira; Alimin Alwi; Najamuddin (International journal of technology and education research, 2026)
This study aims to analyze the deep learning paradigm as a pedagogical strategy for strengthening multicultural education in Indonesia. The main problem identified is that the current implementation of multicultural education in schools tends to be normative-theoretical, resulting in the value of tolerance often being understood only textually without any concrete internalization of attitudes. Furthermore, previous studies on deep learning have focused more on cognitive achievement or critical thinking skills without specifically linking them to the context of Indonesia’s cultural plurality. Using library research, this study explores carious relevant literature to formulate a conceptual foundation for developing learning practices. The result indicate that a deep learning approach that integrates the principles of mindful, meaningful, and joyful learning is capable of transforming diversity issues into an authentic and reflective learning context. The novelty of this research lies in the synthesis of aspects of thought, heart, feeling, and body within a multicultural framework, enabling students not only to master material but also to internalize the values of inclusivity. This strategy offers a solution to the dominance of conventional learning, enabling a generation that is academically intelligent and possesses sustainable multicultural awareness.